Current practices and perspectives on the integration of contrast agents in MRI-guided radiation therapy clinical practice: A worldwide survey. (May 2023) - Boldrini, Luca; Alongi, Filippo; Romano, Angela; Charles Davies, Diepriye; Bassetti, Michael; Chiloiro, Giuditta; Corradini, Stefanie; Gambacorta, Maria Antonietta; Placidi, Lorenzo; Tree, Alison C.; Westley, Rosalyne; Nicosia, Luca
Highlights: The use of contrast agents in RT can improve the workflow of radiotherapy planning, both in target delineation and in delivery. The use of contrast agent in MRI-guided radiotherapy (MRgRT) using MR Linac is currently not standardised among the various centres equipped with this technology. This survey, administered to centres equipped with MR Linac, was developed to understand the use of contrast agent in the MRgRT workflow and future perspectives. Abstract: Aims: The introduction of on-line magnetic resonance image-guided radiotherapy (MRIgRT) has led to an improvement in the therapeutic workflow of radiotherapy treatments thanks to the better visualization of therapy volumes assured by the higher soft tissue contrast. Magnetic Resonance contrast agents (MRCA) could improve the target delineation in on-line MRIgRT planning as well as reduce inter-observer variability and enable innovative treatment optimization protocols. The aim of this survey is to investigate the utilization of MRCA among centres that clinically implemented on-line MRIgRT technology. Methods: In September 2021, we conducted an online survey consisting of a sixteen-question questionnaire that was distributed to the all the hospitals around the world equipped with MR Linacs. The questionnaire was developed by two Italian 0.35 T and 1.5 T MR-Linac centres and was validated by four other collaborating centres, using a Delphi consensus methodology. Results: The survey was distributed to 52 centres and 43 centres completed it (82.7%). Among these centres, 23 institutions (53.5%) used the 0.35T MR-Linac system, while the remaining 20 (46.5%) used the 1.5T MR-Linac system. According to results obtained, 25 (58%) of the centres implemented the use of MRCA for on-line MRIgRT. Gadoxetate (Eovist®; Primovist®) was reported to be the most used MRCA (80%) and liver the most common site of application (58%). Over 70% of responders agreed/strongly agreed to the need for international guidelines. Conclusions: The use of MRCA in clinical practice presents several pitfalls and future research will be necessary to understand the actual advantage derived from the use of MRCA in clinical practice, their toxicity profiles and better define the need of formulating guidelines for standardising the use of MRCA in MRIgRT workflow.